PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP SIKAP KEPEDULIAN LINGKUNGAN SISWA SEKOLAH DASAR PADA MATERI DAUR ULANG SAMPAH - Lukita Febrian, Ardina; Sholikhan, Sholikhan; Dwi Yasa, Arnelia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted from the concern that environmental topics in elementary schools often stop at conceptual understanding and have not consistently shaped students' willingness to care for their surroundings. The research investigated the contribution of Discovery Learning integrated with Interactive Learning Media to fifth-grade students' environmental care attitudes in a waste-recycling lesson. A quasi-experimental quantitative approach was used with a nonequivalent control group design. The participants were 56 students of SDN Sukun 2 Malang, distributed into an experimental class and a comparison class. The instrument was an attitude scale arranged from cognitive, affective, and conative indicators, supported by classroom observation. Data analysis included normality and homogeneity testing, Independent Samples t-test, N-Gain, and effect-size interpretation. The results showed that the experimental class achieved a higher posttest mean than the control class. The N-Gain in the experimental class reached 0.737, while the effect size was 1.99, indicating a strong practical impact. These findings show that discovery activities supported by interactive visual materials can make the issue of waste more visible, personally meaningful, and emotionally engaging for students. Environmental instruction at the elementary level therefore needs to be designed not merely as knowledge delivery, but as learning that trains students to notice problems, reflect on consequences, and build responsible habits.